Academicians' Career Capital and Career Satisfaction: The Mediation Effect of Research Productivity - Aytekin, Ihsan; Erdil, Oya; Erdogmus, Nihat; Akgun, Ali E. (Edam, 2016)
The competitive advantages of knowledge-producing institutions are their wise, creative, enthusiastic, and excited academicians and their competences. Currently, questions come to the fore as to which variables affect the research performance of university-employed academicians, and what role does research performance have in the relationship of these variables with career satisfaction. In answer to these questions, this study hypothesizes that career competences (capital) will positively affect academic productivity and career satisfaction, and that academic productivity will have a mediator effect on the relationship between career competencies and individual career satisfaction, using the groundwork of the competence-based career theory conceptualized as intelligent career by Arthur, Claman, and DeFillippi. With the aim of empirically testing these hypotheses, as well as hypotheses that establish the sub-dimensions of these research questions, two field studies (including one pre-study) have been carried out on academicians working for universities in Turkey. The results reveal that career capital has significant effects on the research productivity of academicians and that research productivity has a mediator effect on the relationship between career capital and career satisfaction.
Keywords: Research productivity; Academicians; Career competencies; Career satisfaction